2020
DOI: 10.20885/jkki.vol11.iss3.art5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pili protein with molecular mass of 85 kDa Escherichia coli as an adhesin and a hemagglutinin

Abstract: Background: Escherichia coli (E. coli) is a rod-shaped gram-negative bacterium included in Multi Drug Resistant (MDR) bacteria. There are several strategies in place to prevent and treat E. coli bacterial infections to reduce some the incidences of MDR. One of them is the development of a protein-based vaccine. Pili is one of virulence factors in E. coli surface proteins that can mediate attachments of bacteria to host cells (adhesin or hemagglutinin) and can be used as protein-based vaccine candidates. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although there is a lot of evidence that supports the protection of antibodies against polysaccharide capsules, the large number of types causes vaccines from this virulence factor to be less feasible, so it is necessary to develop vaccines from other virulence factors such as fimbriae/pili (Arato et al, 2021;Choi et al, 2020;Lundberg et al, 2012). Our previous research showed that the pili protein K. pneumoniae 65.5 kDa exhibits immunogenic properties, which can hypatinate erythrocytes and can act as adhesin (Agustina et al, 2014(Agustina et al, , 2020Kurniawati et al, 2021;Thanassi et al, 2012), as well as being able to induce cytokines as a sign of the emergence of an immune response (in editing). The cytokine used in this study was interleukin-10 (IL-10).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lot of evidence that supports the protection of antibodies against polysaccharide capsules, the large number of types causes vaccines from this virulence factor to be less feasible, so it is necessary to develop vaccines from other virulence factors such as fimbriae/pili (Arato et al, 2021;Choi et al, 2020;Lundberg et al, 2012). Our previous research showed that the pili protein K. pneumoniae 65.5 kDa exhibits immunogenic properties, which can hypatinate erythrocytes and can act as adhesin (Agustina et al, 2014(Agustina et al, , 2020Kurniawati et al, 2021;Thanassi et al, 2012), as well as being able to induce cytokines as a sign of the emergence of an immune response (in editing). The cytokine used in this study was interleukin-10 (IL-10).…”
Section: Introductionmentioning
confidence: 99%